RECONSTRUCTION OF ROAD TRAFFIC AND TRANSPORT LAWS ON DETERMINING DRIVING AREAS FOR VEHICLES WITH AUTOPILOT SYSTEMS - Dyah Kemala Hayati; Moh Fadli; Dewi Cahyandari (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
One developmentartificial intelligence is a vehicle with an autopilot function. This issue needs to be regulated in Law Number 22 of 2009 concerning Road Traffic and Transportation, which does not accommodate the regulation of determining driving areas for autopilot-based vehicles. The added value of this article is that it discusses the settings for determining driving areas in autopilot-based vehicles. The aim of this research is analyzing the urgency of determining driving areas for vehicles with an autopilot system as well as reconstructing traffic and road transport laws regarding determining driving areas for autopilot-based vehicles. This research uses a normative juridical research method with a conceptual approach, a legislative approach and a comparative approach through a comparison of vehicle regulation laws with AI systems in Germany, South Korea and the United States. The results of this research show that the consideration and importance of determining the driving area in vehicles with the systemAutopilot is the level of safety and vehicle autopilot system, the condition of road infrastructure in Indonesia which must be adjusted to the autopilot system, traffic density in Indonesia and the potential risks and impacts on the safety of other road users. It is necessary to reconstruct the determination of autopilot-based vehicle driving areas in law number 22 of 2009 concerning road traffic and transportation.